Anti-dynamic-load anti-seepage solidified soil material, preparation method and application thereof
Patent Information
- Application Number
- CN202611537133.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-30
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies have problems with insufficient resistance to dynamic loads and seepage at the retaining wall backfill of bridge and gate structures. In particular, steel corrosion is easily caused in high humidity environments, resulting in long-term loss of seepage resistance. Furthermore, the mechanical mismatch between the backfill and the retaining wall can easily lead to fatigue failure.
A dynamic load-resistant and impermeable solidified soil material is adopted, which is composed of quicklime, magnesium sulfate heptahydrate, fly ash and granulated blast furnace slag powder. Water-resistant cementitious phase and ettringite crystals are generated through multiple activation mechanisms. Combined with stiffness transition zone and interlayer anchoring technology, the impermeability and mechanical stability of the material are improved.
It achieves high-efficiency impermeability and dynamic load resistance, good long-term stability, and is suitable for various cohesive soils. It significantly improves the waterproof performance and durability of bridge and gate structures and reduces the risk of steel corrosion.
Smart Images

Figure CN123026416A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water conservancy and transportation engineering technology, specifically relating to a solidified soil material for improving the anti-separation and anti-seepage properties of retaining wall fill at the junction of bridges, sluices and embankments, as well as its preparation method and application. Background Technology
[0002] As a crucial hub integrating water level regulation, flood control, and traffic flow, the bridge and sluice gate structure bears the dual burden of cyclic dynamic loads transmitted from the traffic bridge and hydrostatic pressure from the water level for extended periods. Achieving mechanical stability and impermeability of the backfill at this junction prevents wall-soil separation and contact leakage, thus possessing significant engineering application value for maintaining the overall safety and durability of the dike.
[0003] Currently, for the improvement of high liquid limit clay or poor fill, inorganic binders are often used for chemical solidification in engineering projects. Common technical routes include: First, directly adding quicklime or cement to the soil for mixing and compaction to improve the initial strength and water stability of the soil; Second, introducing soluble chloride salts such as magnesium chloride and calcium chloride as admixtures into the lime-based system to pursue early strength or impermeability; Third, some schemes use a lime-sulfate (such as gypsum, magnesium sulfate) two-component system, utilizing magnesium hydroxide generated in an alkaline environment and ettringite to achieve pore sealing and crystal bridging.
[0004] The existing technology still has the following shortcomings: First, the chloride salt system has inherent defects. In the high-humidity environment behind reinforced concrete retaining walls, chloride ions easily cause steel corrosion; and its reaction byproduct, calcium chloride, has high solubility and is leached away under long-term hydrostatic pressure, causing the porosity of the solidified soil to rebound and its long-term impermeability to be lost.
[0005] Secondly, simple lime solidification suffers from insufficient cementitious phase and poor water resistance. The reaction between lime and clay minerals in volcanic ash is slow and limited, resulting in a small amount of cementitious phase and low strength at 28 days. Unreacted calcium hydroxide poses a risk of leaching in water, and its strength and impermeability decrease significantly under long-term immersion conditions.
[0006] Third, the lime-sulfate two-component system is highly dependent on the activity of in-situ soil minerals. The active aluminum source required for the formation of ettringite depends entirely on the alkali dissolution and release of clay minerals in the in-situ soil. However, the types and reactivity of clay minerals vary greatly among different soil types (montmorillonite and illite have higher activity, while kaolinite has lower activity). In low-activity soils, the amount of ettringite formed is insufficient, resulting in large fluctuations in the system's performance. At the same time, this system lacks a sufficient amount of water-resistant cementitious bulk phase, leading to slow early strength development and weak interlayer bonding.
[0007] Fourth, conventional filling techniques do not consider the mechanical mismatch between the retaining wall (extremely high stiffness) and the backfill (low stiffness). Traffic dynamic stress waves are reflected at the interface (the wave impedance ratio between concrete and compacted backfill can be hundreds of times, and the vertical incident reflection coefficient is close to 1), resulting in stress concentration. Under long-term cyclic action, the wall-soil interface is prone to fatigue failure, leading to through-type separation and leakage cracks.
[0008] Therefore, there is an urgent need for a solidified soil material and its construction method that has excellent resistance to dynamic loads and seepage, and is highly adaptable to in-situ soil. Summary of the Invention
[0009] The purpose of this invention is to provide a dynamic load-resistant and impermeable solidified soil material, its preparation method, and its application, in order to solve the above-mentioned problems existing in the prior art.
[0010] To address the aforementioned problems in the existing technology, the present invention provides the following technical solution: a dynamic load-resistant and impermeable solidified soil material, comprising the following components by mass: 100 portions of in-situ soil to be treated; the in-situ soil to be treated is cohesive soil with a plasticity index of not less than 15. 6-12 parts of slaked lime; Magnesium sulfate heptahydrate, 2-5 parts; Fly ash, 5-15 parts; Granulated blast furnace slag powder, 5-15 parts; Cement, 1-3 parts.
[0011] Preferably, the source of the in-situ soil is cohesive soil backfilled on both sides of the bridge gate chamber and retaining wall, with a compaction degree of not less than 0.93 and a plasticity index of not less than 15.
[0012] Preferably, the effective Ca(OH)2 content in the quicklime is not less than 85%, and the fineness meets the requirement of passing through a 200-mesh sieve; the purity of the magnesium sulfate heptahydrate is not less than 98%.
[0013] Preferably, the cement is ordinary Portland cement with a strength grade of not less than 42.5; The mass ratio of the fly ash to the granulated blast furnace slag powder is 1:3 to 3:1, and the total amount of both shall not exceed 30 parts; preferably 16 to 30 parts.
[0014] Preferably, the mass fraction of the quicklime is determined according to the plasticity index of the in-situ soil to be treated: When the plasticity index is 15-20, the amount of quicklime used is 6-8 parts; When the plasticity index is greater than 20 and less than 25, the amount of quicklime used is 8-10 parts; When the plasticity index is not less than 25, the amount of quicklime used is 10-12 parts; and the mass fraction of the quicklime does not exceed 12 parts. The amount used is based on an effective Ca(OH)2 content of 95%; when the effective content is less than 95%, it is calculated based on an equal amount of effective components and the upper limit of that range is taken.
[0015] It should be noted that in geotechnical engineering practice, clay with a liquid limit of not less than 50% usually has a high plasticity index (generally not less than 20).
[0016] Preferably, when the in-situ soil to be treated is high liquid limit clay with a liquid limit of not less than 50%, the amount of quicklime used is 10-12 parts, and the amount range of plasticity index of 15-20 is not applicable. Preferably, the sum of the mass fractions of the fly ash and the granulated blast furnace slag powder is 16 to 30 parts.
[0017] When the permeability coefficient of the solidified soil material is required to be no greater than 2 × 10⁻⁶ -5 When the flow rate is cm / s, the amount of magnesium sulfate heptahydrate used is 4 to 5 parts.
[0018] Preferably, the microstructure of the solidified soil material contains a water-resistant cementitious phase and a reinforcing phase: the water-resistant cementitious phase is hydrated calcium silicate gel and hydrated calcium aluminate gel, which are generated by the fly ash and granulated blast furnace slag powder under alkaline conditions through pozzolanic reaction and potential hydraulic hydration; the reinforcing phase is needle-shaped ettringite crystals; and nano-sized magnesium hydroxide precipitate is also generated in the micropores of the solidified soil material.
[0019] According to one aspect of this application, a method for preparing and using the above-mentioned dynamic load-resistant and impermeable solidified soil material includes the following steps: Step 1: Material mixing. The in-situ soil to be treated, the quicklime, the magnesium sulfate heptahydrate, the fly ash, the granulated blast furnace slag powder, and the cement are mixed evenly with water to obtain a solidified soil mixture. Step 2: Filling the transition zone. A stiffness transition zone is set at the back interface of the retaining wall of the protected retaining structure, and a solidified soil mixture containing external coarse aggregate is filled in the stiffness transition zone. Step 3: Layered filling and anchoring. The solidified soil mixture prepared in Step 1 is laid in layers behind the stiffness transition zone and compacted. Mixed slurry is sprayed between two adjacent compacted layers, or pre-mixed topsoil containing quicklime, magnesium sulfate heptahydrate, fly ash and granulated blast furnace slag powder is spread to perform interlayer anchoring treatment.
[0020] Preferably, in step two, the thickness of the stiffness transition zone is 50cm, the added coarse aggregate is sand and / or gravel with a maximum particle size of no more than 20mm, and the amount of added coarse aggregate is such that the mass content of particles with a particle size of no less than 0.075mm in the transition zone fill material is no less than 30%; the stiffness transition zone is filled in layers, with a single layer loose thickness of 20-25cm and a compaction degree of no less than 93%.
[0021] Preferably, in step three, the mixed slurry is a suspension slurry prepared by a 15% aqueous solution of magnesium sulfate heptahydrate, quicklime, and cement, wherein the mass ratio of quicklime to cement is (2-4):1; the total amount of quicklime, magnesium sulfate heptahydrate, fly ash, and granulated blast furnace slag powder contained in the premixed soil is 20%.
[0022] Preferably, in step one, the maximum dry density and optimal moisture content of the mixture are determined based on the compaction test before mixing, and the water consumed by dissolving the crystal water of magnesium sulfate heptahydrate, the cement hydration and the formation of ettringite is compensated; after step three is completed, the fill body is moisturized and cured.
[0023] This invention uses the strong alkaline environment provided by quicklime and cement hydration as the activation basis, combined with the sulfate ions provided by magnesium sulfate heptahydrate, to implement multiple activation processes of "alkali activation-sulfate activation-cement hydration" on fly ash and granulated blast furnace slag powder, generating a water-resistant cementitious phase, and simultaneously generating nano-sized magnesium hydroxide precipitate to seal pores and needle-shaped ettringite crystals to bridge and toughen; at the same time, it is combined with the macro-stiffness transition zone filling process to achieve the synergy between micro-water-resistant cement and macro-stiffness buffer.
[0024] According to one aspect of this application, the above-mentioned dynamic load-resistant and impermeable solidified soil material is used in the preparation of water-retaining structures subjected to both traffic dynamic loads and hydrostatic pressure.
[0025] Beneficial effects: (1) Sufficient water-resistant cementitious phase and good long-term stability. The main cementitious phase is composed of the pozzolanic reaction and potential hydraulic hydration products of fly ash and slag powder, supplemented by magnesium hydroxide and ettringite, forming a multi-element interpenetrating structure of "gel skeleton + crystal bridging + nano-sealing". The unconfined compressive strength at 28 days can reach more than 3.2 MPa, and the increase in water leakage after 90 days of immersion does not exceed 5.0%. The long-term water resistance is significantly better than that of simple lime solidification and lime-magnesium sulfate two-component system.
[0026] (2) Excellent impermeability. Example data shows that the permeability coefficient can reach as low as 0.5 × 10⁻⁶. -5 cm / s, compared to blank soil (5.0×10 cm / s). -3 The speed (cm / s) has improved by about three orders of magnitude.
[0027] (3) Excellent resistance to dynamic loads. The cumulative dynamic triaxial deformation can be controlled at 0.35% to 0.60% (as low as 0.35% in Example 4); it is lower than that of the single lime-mixed system (Comparative Example 2, 1.35%) and blank soil (Comparative Example 1, failure); the interlayer direct shear strength can reach 120 to 170 kPa (as high as 170 kPa in Example 4), which is more than 50% higher than that of the single lime-mixed system (Comparative Example 2, 80 kPa), which is beneficial to suppressing wall-soil separation.
[0028] (4) Strong adaptability to in-situ soil. The active aluminum source is guaranteed by admixtures and cement, and does not depend on the activity of clay minerals in the in-situ soil. It is suitable for various types of cohesive soil with a plasticity index of 15 or higher, including high liquid limit clay.
[0029] (5) Resource utilization. Fly ash and granulated blast furnace slag powder are both industrial solid wastes. This invention realizes "waste treatment with waste", with significant economic and environmental benefits. Attached Figure Description
[0030] Figure 1 This is a comparison chart of the 28-day compressive strength of various embodiments and comparative examples of the present invention.
[0031] Figure 2 This is a comparison chart of the 7d-28d compressive strength of various embodiments and comparative examples of the present invention.
[0032] Figure 3 This is a trend graph illustrating the threshold effect of magnesium sulfate dosage in this invention.
[0033] Figure 4 This is a soil property gradient comparison diagram of the present invention.
[0034] Figure 5 This is a comparison chart of the permeability coefficients of this invention. Detailed Implementation
[0035] The present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited thereto.
[0036] Component specifications: The effective Ca(OH)₂ content in the slaked lime is not less than 85%, and the fineness meets the requirement of passing through a 200-mesh sieve (sieve opening 0.075mm); the purity of magnesium sulfate heptahydrate is not less than 98%; the fly ash is Grade II or above dry-discharged ash, and the fineness (45μm sieve residue) is not greater than 25%; the specific surface area of the granulated blast furnace slag powder is not less than 400m². 2 / kg, with an activity index (28d) of not less than 75%; the cement is PO42.5 ordinary Portland cement.
[0037] Example 1 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by weight, comprises: 100 parts of the in-situ soil to be treated (clay with a plasticity index of 22), 8 parts of quicklime, 3 parts of magnesium sulfate heptahydrate, 10 parts of fly ash, 10 parts of granulated blast furnace slag powder, and 2 parts of cement. The in-situ soil is sourced from the cohesive soil backfilled on both sides of the bridge gate chamber and retaining wall, with a compaction degree of not less than 0.93 and a plasticity index of not less than 15.
[0038] The solidification mechanism in this embodiment is as follows: The dissolution of quicklime provides a strongly alkaline environment with a pH not lower than 12.4, simultaneously replenishing calcium hydroxide and generating hydrated calcium silicate gel during cement hydration; fly ash and granulated blast furnace slag powder undergo pozzolanic reaction and potential hydraulic hydration under alkali and sulfate activation, generating a water-resistant cementitious phase mainly composed of hydrated calcium silicate gel and hydrated calcium aluminate gel. After dissolution of magnesium sulfate heptahydrate, Mg²⁺… + It rapidly precipitates into nano-sized magnesium hydroxide in a strongly alkaline environment, effectively blocking capillary channels in situ; SO4² - It combines with calcium ions to form gypsum dihydrate. Gypsum, acting as a sulfate carrier, reacts with aluminate ions released from alkali dissolution and calcium hydroxide to form needle-like ettringite crystals. The aluminum source is provided by fly ash, slag powder, and the aluminum component in cement. The reaction formula is as follows: MgSO47H2O+Ca(OH)2→Mg(OH)2↓+CaSO42H2O↓+5H2O; Ca6Al2(SO4)3(OH) 12 26H2O (ettringite) is produced by Al(OH)4 - Ca 2+ SO4 2- It is produced under strongly alkaline conditions.
[0039] The preparation and construction method of the dynamic load-resistant and impermeable solidified soil material in this embodiment includes the following steps: Step 1: Material Mixing. Because this formula contains multiple hydration reaction components, the compaction test of the mixture is first repeated according to the "Standard for Geotechnical Testing Methods" GB / T 50123 to determine its maximum dry density and optimum moisture content. The in-situ soil to be treated, quicklime, magnesium sulfate heptahydrate, fly ash, granulated blast furnace slag powder, and cement are then mixed evenly with water according to the above formula. The amount of water used for mixing is increased by approximately 1–2 percentage points from the optimum moisture content after compaction to compensate for the continuous consumption of liquid water due to cement hydration, the pozzolanic reaction of admixtures, and the formation of ettringite. The water of crystallization released when magnesium sulfate heptahydrate dissolves (approximately 51% of the mass of magnesium sulfate heptahydrate) can partially compensate for the above consumption, but its release is insufficient to cover all the water required for hydration; therefore, additional water is still needed. After the mixture is evenly mixed, the solidified soil mixture is obtained.
[0040] Step Two: Transition Zone Filling. A 50cm thick rigid transition zone is set at the back interface of the retaining wall of the protected retaining structure. The transition zone is filled with a solidified soil mixture containing added coarse aggregate: the added coarse aggregate is natural sand and gravel (maximum particle size not greater than 20mm), with an admixture of 30% of the mixture mass, so that the mass content of particles with a particle size of not less than 0.075mm in the transition zone fill material is not less than 30%; the transition zone is filled in two layers, with a loose layer thickness of 25cm and a compaction degree of not less than 93%.
[0041] Step 3: Layered Filling and Anchoring. Behind the stiffness transition zone, lay the solidified soil mixture prepared in Step 1 in layers, with a loose layer thickness of 25cm and a compaction degree of not less than 93%. A mixed grout is sprayed between adjacent compacted layers for interlayer anchoring. The mixed grout is a suspension prepared from a 15% (w / w) aqueous solution of magnesium sulfate heptahydrate, quicklime, and cement (the mass ratio of quicklime to cement is 3:1). The spraying amount is based on covering the interlayer interface (approximately 1.5-2.5 kg / m²). 2 After the filling is completed, the soil should be kept moist for at least 7 days.
[0042] The preparation method of the mixed slurry is as follows: first, dissolve magnesium sulfate heptahydrate in water to prepare a solution with a mass concentration of 15%, then add quicklime and cement (mass ratio 3:1) and stir evenly. The total solid content of the slurry is 25% to 35% (including magnesium sulfate heptahydrate converted solids). Stir until there are no lumps before use.
[0043] The main function of the stiffness transition zone is to alleviate the abrupt change in stiffness at the retaining wall-fill interface and improve deformation compatibility under dynamic loading conditions, rather than to enhance the static interlayer shear strength. As shown in Table 2, the interlayer direct shear strength of Example 1 and Comparative Example 7 (without a transition zone) are similar (145 kPa and 143 kPa), but the cumulative dynamic triaxial deformation differs significantly (0.45% and 2.40%). This indicates that the engineering contribution of the transition zone mainly lies in suppressing the cumulative plastic deformation at the retaining wall-fill interface under cyclic dynamic loading, rather than changing the static shear bearing capacity.
[0044] Example 2 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass, comprises: 100 parts of the in-situ soil to be treated (silty clay with a plasticity index of 15), 6 parts of quicklime, 2 parts of magnesium sulfate heptahydrate, 8 parts of fly ash, 8 parts of granulated blast furnace slag powder, and 1.5 parts of cement.
[0045] The preparation and construction methods are the same as in Example 1. In step one, the components are weighed and mixed according to the dosages of this example. This example corresponds to the low plasticity end formulation, verifying the applicability of the material system to soils with a lower limit of plasticity index.
[0046] Example 3 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass, comprises: 100 parts of the in-situ soil to be treated (high liquid limit clay with a plasticity index of 25 and a liquid limit of 52%), 10 parts of quicklime, 4 parts of magnesium sulfate heptahydrate, 12 parts of fly ash, 12 parts of granulated blast furnace slag powder, and 2 parts of cement.
[0047] The preparation and construction methods are the same as in Example 1. This example verifies the formulation for high liquid limit clay zones and the high zone mix proportions based on plasticity index grading.
[0048] Example 4 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass, comprises: 100 parts of the in-situ soil to be treated (extremely high liquid limit clay with a plasticity index of 32.5 and a liquid limit of 65%), 12 parts of quicklime, 5 parts of magnesium sulfate heptahydrate, 15 parts of fly ash, 15 parts of granulated blast furnace slag powder, and 3 parts of cement.
[0049] The preparation and construction methods are the same as in Example 1. This example verifies the formulation for extremely high liquid limit clay zones (using the upper limit of 12 parts of quicklime).
[0050] Example 5 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass, comprises: 100 parts of the in-situ soil to be treated (clay with a plasticity index of 20), 8 parts of quicklime, 5 parts of magnesium sulfate heptahydrate, 10 parts of fly ash, 10 parts of granulated blast furnace slag powder, and 2.5 parts of cement.
[0051] The preparation and construction methods are the same as in Example 1. This example verifies the high impermeability specialized formula: magnesium sulfate heptahydrate is taken at the upper limit of 5 parts to ensure that the permeability coefficient is not greater than 2×10. -5 The required speed is cm / s.
[0052] Example 6 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass, comprises: 100 parts of the in-situ soil to be treated (clay with a plasticity index of 22), 8 parts of quicklime, 3 parts of magnesium sulfate heptahydrate, 15 parts of fly ash, 5 parts of granulated blast furnace slag powder, and 2 parts of cement.
[0053] The preparation and construction methods are the same as in Example 1. This example verifies the dominant fly ash ratio (fly ash to slag powder mass ratio 3:1) and examines the contribution of the pozzolanic reaction pathway.
[0054] Example 7 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass parts, comprises: 100 parts of the in-situ soil to be treated (clay with a plasticity index of 22), 8 parts of quicklime, 3 parts of magnesium sulfate heptahydrate, 5 parts of fly ash, 15 parts of granulated blast furnace slag powder, and 2 parts of cement.
[0055] The preparation and construction methods are the same as in Example 1. This example verifies the dominant proportion of slag powder (mass ratio of fly ash to slag powder 1:3) and examines the contribution of potential hydraulic hydration pathways.
[0056] Example 8 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass parts, comprises: 100 parts of the in-situ soil to be treated (silty clay with a plasticity index of 18), 6 parts of quicklime, 4 parts of magnesium sulfate heptahydrate, 12 parts of fly ash, 8 parts of granulated blast furnace slag powder, and 1 part of cement.
[0057] The preparation and construction methods are the same as in Example 1. This example verifies the anti-permeability effect of magnesium sulfate heptahydrate with medium to high values (4 parts) under low alkali and low cement conditions, and covers the lower limit range of cement dosage.
[0058] Example 9 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass parts, comprises: 100 parts of the in-situ soil to be treated (high liquid limit clay with a plasticity index of 30), 12 parts of quicklime, 2 parts of magnesium sulfate heptahydrate, 5 parts of fly ash, 12 parts of granulated blast furnace slag powder, and 1 part of cement.
[0059] The preparation and construction methods are the same as in Example 1. This example verifies the performance of granulated blast furnace slag powder with potential hydraulic hydration as the dominant pathway under a high-alkali and low-sulfate combination.
[0060] Example 10 This embodiment provides a dynamic load-resistant and impermeable solidified soil material, which, by mass parts, comprises: 100 parts of the in-situ soil to be treated (silty clay with a plasticity index of 16), 6 parts of quicklime, 3 parts of magnesium sulfate heptahydrate, 15 parts of fly ash, 5 parts of granulated blast furnace slag powder, and 3 parts of cement.
[0061] In step three, in addition to spraying the mixed slurry, interlayer anchoring can also be achieved by spreading pre-mixed topsoil. The pre-mixed topsoil uses in-situ soil as the matrix, incorporating quicklime, magnesium sulfate heptahydrate, fly ash, and granulated blast furnace slag powder, with a total admixture amount of 20% of the pre-mixed topsoil mass. A thin layer is spread on the compacted layer surface, moistened with water, and then the upper layer of soil is compacted. This method is equivalent to spraying the mixed slurry in terms of interlayer chemical anchoring, as they share the same active components and reaction mechanisms. Those skilled in the art can choose the appropriate method based on site conditions (availability of slurry preparation equipment, climate conditions, etc.).
[0062] The preparation and construction methods are the same as in Example 1. This example verifies the performance of fly ash pozzolanic reaction as the dominant pathway under the low alkali and high cement combination, which is the reverse combination of hydrated lime and cement dosage in Example 9.
[0063] Referring to Table 1, the formulations of each embodiment and comparative example are as follows: Table 1 Comparison of Formulations of Examples and Comparative Examples (Unit: Parts by Mass)
[0064] Table 2 Summary of Performance Test Data for Examples and Comparative Examples
[0065] Test methods: Unconfined compressive strength was determined according to GB / T 50123 (specimen diameter 39.1 mm, height 80 mm, standard curing); constant head permeability coefficient was determined according to GB / T 50123; dynamic triaxial cumulative deformation was determined according to GB / T 50123 dynamic triaxial test (specimen includes simulated retaining wall rigid interface, confining pressure 100 kPa, axial cyclic stress amplitude 50 kPa, frequency 1 Hz, 10,000 cycles, cumulative axial strain); interlaminar direct shear strength was determined according to GB / T 50123 direct shear test (specimen is a double-layer molded specimen with interlaminar anchoring interface, quick shear); 90-day immersion leakage increase was the percentage increase in constant head permeability coefficient before and after immersion, after 28 days of standard curing.
[0066] The following combination Figures 1 to 5 Describe the mechanism and effects of the present invention: Comparison of microscopic characteristics of improperly proportioned groups: Comparative Example 2 (single lime admixture) showed only a small amount of amorphous CSH gel, no magnesium hydroxide or ettringite, and sparse cementitious phase; Comparative Example 3 (chloride system) produced magnesium hydroxide, but contained highly soluble calcium chloride, and the porosity increased dramatically after leaching; Comparative Example 4 (excess sulfate) showed excessive growth of ettringite, with large crystals and local aggregation, leading to microscopic expansion and cracking; Comparative Example 5 (insufficient lime) showed insufficient alkali activation, resulting in a small amount of gel phase and a loose structure; Comparative Example 8 (no cement) and Comparative Example 9 (no admixture) showed significantly less gel phase than Example 1.
[0067] (1) Calculation of ettringite pore capacity (taking Example 1, 3 parts of magnesium sulfate heptahydrate, molar mass 246.47 g / mol as an example): Every 100 parts of in-situ soil can provide about 0.0122 mol of sulfate ions. The formation of ettringite requires 3 mol of sulfate ions / mol, and the maximum amount of ettringite that can be formed is about 0.0041 mol, which translates to a solid phase volume of about 2.9 cm³. 3 100 parts compacted clay (dry density approximately 1.6 g / cm³) 3 The pore volume (with a porosity ratio of 0.5-0.7) is approximately 20-25 cm³. 3Etnacite only fills about 12-14% of the pore volume. Even with the addition of nano-magnesium hydroxide (approximately 0.0122 mol) and CSH / CAH gel, the total volume is still below the pore capacity limit. Comparative Example 4 (8 parts magnesium sulfate heptahydrate, approximately 0.032 mol sulfate, ettringite volume approximately 7.7 cm³) 3 The presence of magnesium sulfate heptahydrate (approximately 31-38% of the pore volume) resulted in a 28-day strength degradation and a sharp deterioration in permeability, verifying the threshold effect of sulfate dosage. In actual filling conditions, the solidified soil, under the lateral constraint of the retaining wall and the confining pressure generated by the weight of the overlying soil, further suppressed the free expansion tendency of ettringite. Therefore, limiting the dosage of magnesium sulfate heptahydrate to 2-5 parts ensured both the bridging and toughening effect and pore-filling effect of ettringite, while controlling its formation within the pore capacity threshold. No net expansion deformation was observed within the dosage range of this invention.
[0068] (2) Alkali Supply Calculation (Taking Example 1 as an example): The following calculation is based on the first-grade quicklime (effective Ca(OH)2 content of about 95%) actually used in the example. When quicklime with an effective Ca(OH)2 content of 85% is used, the alkali supply is reduced accordingly, but still meets the alkali demand for 28 days (supply of about 0.089 mol > demand of about 0.084 mol). The baseline value of alkali demand for 28 days is about 0.072 mol, and the conservative upper limit is about 0.084 mol. The alkali reserve is about 0.4 parts equivalent, which can be guaranteed for subsequent hydration by appropriately extending the moist curing time (not less than 14 days). The alkali reserve of Example 4 (12 parts quicklime) is the most sufficient, and its 28-day strength and impermeability are also the best, which is consistent with the above calculation.
[0069] (3) Aluminum source supply calculation (taking Example 1 as an example): Fly ash (Al2O3 content about 30%, 10 parts) can provide about 0.058 mol of active aluminum, slag powder (Al2O3 content about 13%, 10 parts) can provide about 0.025 mol, and cement (2 parts) can provide about 0.002 mol, for a total active aluminum supply of about 0.085 mol, while the formation of ettringite only requires about 0.0082 mol of aluminum, which is about 10 times more. Therefore, the formation of ettringite in this invention does not depend on the aluminum dissolution of in-situ clay minerals and is also applicable to low-activity kaolinite soils.
[0070] (4) Cement-sulfate compatibility calculation: The SO3 content (according to the national standard limit of 3.5%) in 2 parts of cement is approximately 0.07 parts, which is far below the cement stability risk level; the sulfate ions provided by magnesium sulfate heptahydrate preferentially react with lime to form gypsum, Mg 2+ Because the solubility of magnesium hydroxide is extremely low (5.6 × 10⁻⁶), -12 The precipitation was rapid and complete, leaving free Mg in the system. 2+The concentration is extremely low, and it will not cause magnesium salt erosion in cement hydration, nor will it induce rapid setting. Comparative Examples 4 and 10 respectively verified the upper limits of sulfate and cement dosage; performance degradation occurred when the limits were exceeded.
[0071] The above examples and comparative examples show that the present invention constructs a water-resistant cementitious system through multiple activation processes of "alkali activation-sulfate activation-cement hydration". Combined with the interlayer grout anchoring and stiffness transition zone process, it is significantly superior to blank soil, lime-admixed system, chloride salt system and control system without admixtures / cement in terms of compressive strength, impermeability, dynamic load deformation resistance, interlayer shear resistance and long-term water resistance stability.
[0072] The 28-day strength development in Comparative Example 10 was lower than expected (only 68.8% of that in Example 1), presumably due to incomplete hydration of excessive cement and delayed expansion of ettringite.
[0073] In this comparative example, the cement content reached 8 parts, which is 4 times that of Example 1. The excessive cement content led to a sharp increase in hydration water demand. Without a simultaneous significant increase in the mixing moisture content, the actual water-cement ratio was low, resulting in incomplete cement hydration and the formation of micro-cracks due to drying shrinkage. This caused a significant decrease in the 28-day unconfined compressive strength (2.20 MPa) compared to Example 1 (3.20 MPa). Simultaneously, the tricalcium aluminate (C3A) in the excess cement continued to react with sulfate ions in the system in the later stages, producing a delayed ettringite expansion effect, further deteriorating the permeability coefficient and dynamic load stability. Therefore, the cement content should not exceed 3 parts.
[0074] On the soil property gradient (Examples 2→5→1→3→4, Ip=15→32.5), the 28-day strength monotonically increased from 2.40 MPa to 4.00 MPa, and the dynamic deformation decreased from 0.60% to 0.35%, verifying the rationality of the quicklime Ip grading rule; all indicators of the Ip=15 lower limit group (Example 2) were at the lower limit of the example interval, consistent with the "plasticity index lower limit boundary verification" positioning. On the fly ash to slag ratio path, the slag-dominated Example 7 > the equal ratio scheme of Example 1 > the fly ash-dominated scheme of Example 6, which is consistent with the mechanism that slag powder has both alkali-activated and sulfate-activated dual responses and a higher activity index.
[0075] Unlike traditional technologies, the technical effects that this application can achieve include: (1) Multiple activations and formation of water-resistant cementitious phase. The dissolution of quicklime in water provides a strongly alkaline environment with a pH of not less than 12.4 (the pH of a saturated calcium hydroxide solution is about 12.4-12.6). Cement hydration releases calcium silicate hydrate gel while further replenishing calcium hydroxide. The two together constitute the alkaline activation basis. The active silica and active alumina in fly ash undergo pozzolanic reaction in a strongly alkaline environment. Granulated blast furnace slag powder undergoes potential hydraulic hydration under the combined action of alkali activation and sulfate activation, generating a water-resistant cementitious phase mainly composed of calcium silicate hydrate (CSH) gel and calcium aluminate hydrate (CAH) gel. This cementitious phase is a sparingly soluble hydration product with high stability in water. It constitutes the framework of the long-term water resistance and impermeability of the solidified soil, which helps to alleviate the defects of insufficient cementitious phase solidification by simple lime and easy dissolution of calcium hydroxide.
[0076] (2) Magnesium hydroxide blocking and calcite bridging. After magnesium sulfate heptahydrate dissolves, Mg 2+ It rapidly precipitates into nano-sized magnesium hydroxide in a strongly alkaline environment. Its high specific surface area allows it to deposit in situ between clay particles and within micropores, physically sealing capillary channels; SO4 2- It then combines with calcium ions to form gypsum dihydrate (CaSO42H2O). Gypsum acts as a sulfate carrier, and then reacts with the aluminate ions Al(OH) released by alkali dissolution. 4- It reacts with calcium hydroxide to form needle-like ettringite crystals (Ca6Al2(SO4)3(OH)). 12 The fly ash (Al2O3 content approximately 20-35%), granulated blast furnace slag powder (Al2O3 content approximately 10-18%), and cement (containing tricalcium aluminate) introduced in this invention provide an active aluminum source far exceeding the required amount for ettringite formation. This helps to suppress dependence on the activity of in-situ clay minerals and enhances the system's adaptability to low-activity soils.
[0077] (3) Early strength and anchoring enhancement effect of a small amount of cement. The cement content is only 1-3 parts (accounting for 1-3% of the mass of the in-situ soil), which is much lower than the 8-15% content of conventional cement soil. Its function is to: provide early hydration strength to make up for the slow strength development in the early stage of pozzolanic reaction; supplement calcium hydroxide and calcium source to enhance alkaline activation; and improve the early bond strength of interlayer anchoring grout. Excessive cement is not advisable due to concentrated heat of hydration, drying shrinkage cracking and poor economy (see Comparative Example 10).
[0078] (4) Macroscopic stiffness transition and interlayer anchoring. A stiffness transition zone containing added coarse aggregate is set on the back of the retaining wall. The stiffness gradient of “retaining wall-coarse solidified soil-fine solidified soil” reduces the sudden change in interface wave impedance and alleviates dynamic stress concentration. Chemical anchoring is carried out by spraying a mixed slurry containing quicklime, magnesium sulfate heptahydrate and a small amount of cement (or spreading pre-mixed soil) between layers. This helps to reduce the formation of incompletely hydrated soft and lubricated surfaces in the dry powder process and helps to suppress weak interlayer slip surfaces.
Claims
1. A dynamic load-resistant and impermeable solidified soil material, characterized in that, By weight, it contains the following components: 100 portions of in-situ soil to be treated; the source of the in-situ soil to be treated is cohesive soil backfilled on both sides of the bridge gate chamber and retaining wall, with a compaction degree of not less than 0.93 and a plasticity index of not less than 15; 6-12 parts of slaked lime; Magnesium sulfate heptahydrate, 2-5 parts; Fly ash, 5-15 parts; Granulated blast furnace slag powder, 5-15 parts; Cement, 1-3 parts.
2. The dynamic load-resistant and impermeable solidified soil material according to claim 1, characterized in that, The slaked lime contains no less than 85% effective Ca(OH)2 and has a fineness that meets the requirement of passing through a 200-mesh sieve; the magnesium sulfate heptahydrate has a purity of no less than 98%.
3. The dynamic load-resistant and impermeable solidified soil material according to claim 1, characterized in that, The cement is ordinary Portland cement with a strength grade of not less than 42.5; The mass ratio of the fly ash to the granulated blast furnace slag powder is 1:3 to 3:1, and the total amount of both does not exceed 30 parts.
4. The dynamic load-resistant and impermeable solidified soil material according to claim 1, characterized in that, The mass fraction of quicklime is determined according to the plasticity index of the in-situ soil to be treated: When the plasticity index is 15-20, the amount of quicklime used is 6-8 parts; When the plasticity index is greater than 20 and less than 25, the amount of quicklime used is 8-10 parts; When the plasticity index is not less than 25, the amount of quicklime used is 10-12 parts; and the mass fraction of the quicklime does not exceed 12 parts.
5. The dynamic load-resistant and impermeable solidified soil material according to claim 4, characterized in that, When the in-situ soil to be treated is high liquid limit clay with a liquid limit of not less than 50%, the amount of quicklime used is 10-12 parts, and it is not applicable to the dosage range of plasticity index of 15-20. When the permeability coefficient of the solidified soil material is required to be no greater than 2 × 10⁻⁶ -5 When the flow rate is cm / s, the amount of magnesium sulfate heptahydrate used is 4 to 5 parts.
6. The dynamic load-resistant and impermeable solidified soil material according to claim 1, characterized in that, The microstructure of the solidified soil material contains a water-resistant cementitious phase and a reinforcing phase: The water-resistant cementitious phase is hydrated calcium silicate gel and hydrated calcium aluminate gel, which are generated by the fly ash and the granulated blast furnace slag powder in an alkaline environment through pozzolanic reaction and potential hydraulic hydration. The reinforcing phase is needle-shaped ettringite crystals; nano-sized magnesium hydroxide precipitate is also generated in the micropores of the solidified soil material.
7. A method for preparing and using the dynamic load-resistant and impermeable solidified soil material according to claim 1, characterized in that, Includes the following steps: Step 1: Mix the in-situ soil to be treated, the quicklime, the magnesium sulfate heptahydrate, the fly ash, the granulated blast furnace slag powder, and the cement with water until uniform to obtain a solidified soil mixture; Step 2: Set a stiffness transition zone at the back interface of the retaining wall of the protected retaining structure, and fill the stiffness transition zone with a solidified soil mixture containing added coarse aggregate; Step 3: Lay the solidified soil mixture prepared in Step 1 in layers behind the stiffness transition zone and compact it. Spray the mixed slurry between two adjacent compacted layers, or spread the pre-mixed soil containing quicklime, magnesium sulfate heptahydrate, fly ash and granulated blast furnace slag powder to perform interlayer anchoring treatment.
8. The method according to claim 7, characterized in that, In step two, the thickness of the stiffness transition zone is 50cm, and the added coarse aggregate is sand and / or gravel with a maximum particle size of no more than 20mm. The amount of added coarse aggregate is such that the mass content of particles with a diameter of not less than 0.075 mm in the transition zone fill material is not less than 30%. The stiffness transition zone is filled in layers, with a single layer loose thickness of 20-25cm and a compaction degree of not less than 93%.
9. The method according to claim 7, characterized in that, In step three, the mixed slurry is a suspension slurry prepared by mixing a 15% magnesium sulfate heptahydrate aqueous solution with quicklime and cement, wherein the mass ratio of quicklime to cement is (2-4):1; the total amount of quicklime, magnesium sulfate heptahydrate, fly ash and granulated blast furnace slag powder contained in the premixed soil is 20%; In step one, the maximum dry density and optimal moisture content of the mixture are determined based on the compaction test before mixing, and the water consumed by dissolving the crystal water of magnesium sulfate heptahydrate, the cement hydration and the formation of ettringite is compensated; after step three is completed, the fill body is moisturized and cured.
10. The application of the dynamic load-resistant and impermeable solidified soil material as described in claim 1 in the preparation of water-retaining structures subjected to both traffic dynamic loads and hydrostatic pressure.
